2017
DOI: 10.1002/hyp.11091
|View full text |Cite
|
Sign up to set email alerts
|

Comparing catchment hydrologic response to a regional storm using specific conductivity sensors

Abstract: A better understanding of stormwater generation and solute sources is needed to improve the protection of aquatic ecosystems, infrastructure, and human health from large runoff events. Much of our understanding of water and solutes produced during stormflow comes from studies of individual, small headwater catchments. This study compared many different types of catchments during a single large event to help isolate landscape controls on streamwater and solute generation, including human‐impacted land cover. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…A network of in situ, high‐frequency sensors characterized specific conductance in streams, rivers, and storm drainage infrastructure in diverse land cover throughout New Hampshire, eastern Massachusetts, and western Maine (Contosta et al, 2017; Inserillo et al, 2017). The Lotic Volunteers Temperature, Electrical Conductivity, and Stage (LoVoTECS) network collected data throughout the study region from 2011 to 2016.…”
Section: Methodsmentioning
confidence: 99%
“…A network of in situ, high‐frequency sensors characterized specific conductance in streams, rivers, and storm drainage infrastructure in diverse land cover throughout New Hampshire, eastern Massachusetts, and western Maine (Contosta et al, 2017; Inserillo et al, 2017). The Lotic Volunteers Temperature, Electrical Conductivity, and Stage (LoVoTECS) network collected data throughout the study region from 2011 to 2016.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the threshold value chosen should not be limited by the volumetric soil moisture content. While our research used the relative saturation index based on HOF theory, other parameters, such as hydraulic conductivity, might be more reasonable 41,42,50,51 . However, the methods mentioned above should be tested and verified in future research initiatives, which are beyond the scope of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Because rainfall EC data were not available for each individual event, an average EC of 8 μS/cm was used in the computations for all events (range: 3–20 μS/cm; EC < 10 μS/cm for 16 out of 18 samples). Several recent studies have shown that, despite not being a conservative tracer, EC can be useful for hydrograph separation (Inserillo et al, ; Pellerin et al, ; Robinson et al, ). However, other studies have shown that there can be substantial differences between EC‐ and isotope‐based hydrograph separation results for some events (Litt et al, ; Penna et al, ).…”
Section: Methodsmentioning
confidence: 99%